The Favorable Prognostic Factors for Superior Sulcus Tumor: A Systematic Review and Meta-Analysis - Hao, Xiaohu; Wang, Zihuai; Cheng, Diou; Zhou, Jian; Chen, Nan; Pu, Qiang; Liu, Lunxu (Frontiers in Oncology, 2020)
Background: Superior sulcus tumor is a rare non-small cell lung cancer with poor prognosis. Exploring the potential prognostic factors of patients with superior sulcus tumor and adopting individualized treatment for patients with different prognostic factors are of great significance for the prolongation of patients' lives. To figure out the prognostic factors of upper sulcus tumors, a meta-analysis was conducted. Method: We searched all the articles published until January 2020 in PubMed, Embase, and Web of Science databases, and the search strategy included the following terms, combining superior sulcus tumor and prognosis. Hazard ratio (HR) with associated confidential interval (CI) was evaluated for the purpose of investigating prognostic factors for superior sulcus tumor. STATA 16.0 was used for analysis of extracted data and assessment of publication bias. Result: Fifteen eligible studies, which had 1,009 patients with superior sulcus tumor, were included in this meta-analysis. The studies were published between 1994 and 2018, and the patient recruitment periods ranged from 1974 to 2016. The median follow-up time ranged from 18 to 95 months. The meta-analysis indicated that lower T stage (HR, 1.63; 95% CI, 1.35–1.97), lower N stage (HR, 3.08; 95% CI: 2.37–3.99), negative surgical margin (HR, 0.25; 95% CI, 0.17–0.38), and pathologic complete response (HR, 0.55; 95% CI, 0.39–0.77) were favorable prognostic factors. Conclusion: We found that T stage, N stage, surgical margin, and pathologic complete response are prognostic factors for superior sulcus tumor. To reach a better long-term survival, patients with these negative prognostic factors may need a more aggressive treatment, while more studies should be conducted to further validate these results and explore a more effective treatment.